2018
DOI: 10.1021/acs.jpclett.8b00238
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Catalytic Proton Donors and Nucleophiles in Enzymes: How Adding Dynamics Helps Elucidate the Structure–Function Relationships

Abstract: Despite the relevance of understanding structure-function relationships, robust prediction of proton donors and nucleophiles in enzyme active sites remains challenging. Here we tested three types of state-of-the-art computational methods to calculate the p K's of the buried and hydrogen bonded catalytic dyads in five enzymes. We asked the question what determines the p K order, i.e., what makes a residue proton donor vs a nucleophile. The continuous constant pH molecular dynamics simulations captured the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(111 citation statements)
references
References 47 publications
21
88
0
Order By: Relevance
“…Since could in principle donate a proton to along the formed hydrogen bond, but does not donate a proton to since there is no hydrogen bond between them, should be more willing to lose its own proton (lower ) as it already partially shares the proton from . This general trend of increasing hydrogen bonds leading to lower has been noted previously within many biological contexts ( 55 , 56 ) Therefore, the free energy change of the proton transfer process from to should be positive, and any singly protonated state should place the proton on the B monomer, creating the state.…”
Section: Resultssupporting
confidence: 69%
“…Since could in principle donate a proton to along the formed hydrogen bond, but does not donate a proton to since there is no hydrogen bond between them, should be more willing to lose its own proton (lower ) as it already partially shares the proton from . This general trend of increasing hydrogen bonds leading to lower has been noted previously within many biological contexts ( 55 , 56 ) Therefore, the free energy change of the proton transfer process from to should be positive, and any singly protonated state should place the proton on the B monomer, creating the state.…”
Section: Resultssupporting
confidence: 69%
“…To further test the ability of single-pH simulations to quantitatively reproduce the experi- mental apparent pK a 's of coupled sites in enzymes, we performed titration simulations of BACE1, which is more than three times as large as HEWL, a frequently used benchmark protein for pK a calculations, 16,32 and more than twice as large as xylanase, the largest protein among the 10 benchmark proteins studied here. Most importantly, the aspartyl dyad of BACE1 (Asp32 and Asp228) is subject to much stronger hydrogen bonding than the linked residues in SNase and RNase H. 51 Our previous replica-exchange simulations with an EAF of 2 ps −1 35 and the hybrid-solvent continuous CpHMD in CHARMM 12 correctly predicted the pK a order of the dyad but underestimated the two macroscopic pK a 's and magnitude of their splitting. The current single-pH simulations also reproduced the experimental pK a order; however, compared to the experimental data, the macroscopic pK a assigned to Asp32 is too high by 1.4 units, and Asp228, which is the dyad residue with the lower pK a did not protonate even at pH 1 (the lowest simulation pH).…”
Section: Comparison Of Single-ph and Replica-exchange Simulations Witmentioning
confidence: 89%
“…Interestingly, for both proteins, the nucleophile (residue with the lower pK a ) has a larger SASA and number of hydrogen bonds compared to the proton donor (higher pK a ), in agreement with the findings from CpHMD simulations using the CHARMM force field and the GBSW model. 49 Having established that a high EAF leads to insufficient conformational relaxation for linked residues, we wondered if the pK a 's of other independent residues are affected as well. A comparison of the pK a 's from the SNase simulations with different EAFs and single pH values (no exchange) showed that, although the differences are much smaller than for the couple residues, the pK a 's from the two slower exchange (EAF of 1 and 0.5 ps -1 ) simulations agree with each other and with the single-pH simulations much better as compared to the fast exchange (EAF of 2 ps -1 ) simulations (Table S1).…”
Section: A High Exchange Attempt Frequency Leads To Insufficient Confmentioning
confidence: 99%
“…The current single-pH simulations also reproduced the experimental pK a order; however, Asp228, the residue with the lower pK a did not protonate even at pH 1 (the lowest simulation pH), due to the persistent hydrogen bond with Asp32 (data not shown). Considering the size of the protein and the strength of the hydrogen bond, 49 significantly longer simulations (than 2 ns) or enhanced sampling may be required. We compared all the single-pH calculated pK a 's and the corresponding replica-exchange 16 results (Table S1).…”
Section: A High Exchange Attempt Frequency Leads To Insufficient Confmentioning
confidence: 99%